Is exposure to personal music players a confounder in adolescent mobile phone use and hearing health studies? - Geza Benke; Christina Dimitriadis; Berihun M. Zeleke; Imo Inyang; Dean McKenzie; Michael J. Abramson (Journal of International Medical Research, 2018)
Objective This study was performed to determine whether exposure to personal music players (PMPs) in the immediate morning prior to hearing testing confounds the association between mobile phone use and hearing thresholds of adolescents. Design In this cohort study of cognitive function in year 7 students (median age 13 years, range 11–14), information regarding the weekly use of mobile phones and the use of PMPs was assessed by a questionnaire. Pure-tone audiometry was used to establish hearing thresholds for all participants. Results Among a cohort of 317 adolescents (60.9% females), 130 were unexposed to PMP use while 33 were exposed to PMP use in the morning prior to hearing testing. No statistically significant difference in hearing threshold shifts was found between adolescents who were and were not exposed to PMP use prior to hearing testing. Likewise, the difference in the use of mobile phones according to the PMP use status was not statistically significant. Conclusion Exposure to PMPs prior to hearing testing did not introduce confounding in the present study of mobile phone use and hearing loss among adolescents.